2015
DOI: 10.1039/c5tc00951k
|View full text |Cite
|
Sign up to set email alerts
|

High quality LED lamps using color-tunable Ce3+-activated yellow-green oxyfluoride solid-solution and Eu3+-doped red borate phosphors

Abstract: Warm white light has been demonstrated using color-tunable Ce3+-activated yellow-green oxyfluoride solid-solution and Eu3+-doped red borate phosphors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The obtained result further demonstrates that the Eu 3+ fluorescent prober still owns the more sensitive identification, even though the content of impurity phase is few on the basis of the XRPD investigation. Nevertheless, the 5 D 0 → 7 F 0 emissions for the highly doped sample broaden, and the four transition peaks could not be clearly identified even if at 78 K. That phenomenon is mainly derived from the energy transfer among Eu 3+ ions, which is usually generated with the increase of the dopant concentration of the lanthanide cations. , As illustrated in Figure d, when altering the excitation wavelength, the area ratio of 5 D 0 → 7 F 0 / 5 D 0 → 7 F 2 and 5 D 0 → 7 F 1 / 5 D 0 → 7 F 2 for x = 0.5 atom % sample displays an alike change tendency with those of x = 0.1 atom % sample. However, the specimen with high Eu 3+ doping shows a smaller variation range about the area ratio of 5 D 0 → 7 F 1 / 5 D 0 → 7 F 2 than that of the specimen with low Eu 3+ doping, suggesting that the phase content of β-Ca 2 SiO 4 in the prepared sample is higher …”
Section: Resultsmentioning
confidence: 95%
“…The obtained result further demonstrates that the Eu 3+ fluorescent prober still owns the more sensitive identification, even though the content of impurity phase is few on the basis of the XRPD investigation. Nevertheless, the 5 D 0 → 7 F 0 emissions for the highly doped sample broaden, and the four transition peaks could not be clearly identified even if at 78 K. That phenomenon is mainly derived from the energy transfer among Eu 3+ ions, which is usually generated with the increase of the dopant concentration of the lanthanide cations. , As illustrated in Figure d, when altering the excitation wavelength, the area ratio of 5 D 0 → 7 F 0 / 5 D 0 → 7 F 2 and 5 D 0 → 7 F 1 / 5 D 0 → 7 F 2 for x = 0.5 atom % sample displays an alike change tendency with those of x = 0.1 atom % sample. However, the specimen with high Eu 3+ doping shows a smaller variation range about the area ratio of 5 D 0 → 7 F 1 / 5 D 0 → 7 F 2 than that of the specimen with low Eu 3+ doping, suggesting that the phase content of β-Ca 2 SiO 4 in the prepared sample is higher …”
Section: Resultsmentioning
confidence: 95%
“…Dai et al . studied the luminescence properties of yellowish green (La,Ca) 3 (Al,Si)O 4 (O,F):Ce 3+ and red Ca 3 La 3 (BO 3 ) 5 :Eu 3+ (CLBO) phosphors by employing the Rietveld refinement, DFT, and pair‐distribution function (PDF) analysis . These studies revealed that substitution of La 3+ (Ca 2+ ) in place of Sr 2+ (Ba 2+ ) was more energetically favorable than La 3+ (Ca 2+ ) in place of Ba 2+ (Sr 2+ ), whereas Ce 3+ ions would occupy the same sites as the La 3+ ions.…”
Section: Development Of New Phosphorsmentioning
confidence: 96%
“…Many host matrices have been explored for their suitability for use in LEDs. For instance, borates, silicates, phosphates, aluminates, and garnets doped with RE ions have been reported. Among the various hosts, phosphate‐based materials have been considered as excellent host matrices for RE ion transitions to exhibit luminescence.…”
Section: Introductionmentioning
confidence: 99%